Effectiveness of the BBV-152 and AZD1222 vaccines among adult patients hospitalized in tertiary hospitals in Odisha with symptomatic respiratory diseases: A test-negative case–control study - Bhattacharya, Debdutta; Kanungo, Srikanta; Palo, Subrata Kumar; Kshatri, Jaya Singh; Pattnaik, Matrujyoti; Ghosal, Shishirendu; Mohapatra, Pranab; Rao, C. Mohan; Sahoo, Avinav; Mishra, Rudra Prasanna; Mishra, Sanghamitra; Mohanta, Amiya Ranjan; et al. (Frontiers in Public Health, 2023)
Two vaccines named BBV-152 (COVAXIN®) and AZD1222 (COVISHIELD™) were deployed against SARS-CoV-2 in India from January 16, 2021. Frontline health-care workers were vaccinated first, followed by the adult population. However, limited data regarding vaccine effectiveness are available on India population. Hence, we aimed to evaluate the effectiveness of two doses for the two common vaccines against COVID-19 infection among hospitalized patients with pulmonary conditions. We adopted a test-negative case-control design on adults who were admitted to six tertiary care hospitals of Odisha. Study participants were hospitalized patients with COVID-19 like pulmonary signs and symptoms. Participants tested positive in RT-PCR for SARS CoV-2 were marked as cases and those who tested negative, were considered as controls. Participants’ age, sex and number of comorbidities were adjusted in logistic regression to calculate the effectiveness of the two vaccines, using the formula: 100*(1-Adjusted Odds Ratio). Between March to July, 2021, data was collected for 1614 eligible adults (864 cases and 750 controls). Of all the participants 9.7% received two doses of covid vaccines. Vaccine effectiveness for two doses of BBV-152 vaccine was 74.0% (50.5% - 86.0%) and for two doses of AZD1222, the effectiveness was found to be 79.0% (65.4% -87.2%). Two doses of either BBV-152 or AZD1222 nCoV-19 vaccine have resulted to be substantially effective in protecting against COVID-19-related infection. As a primary goal, the abstract should render the general significance and conceptual advance of the work clearly accessible to a broad readership.